Increased 30‐day mortality in patients with diabetes undergoing surgery for colorectal cancer. (January 2016) - Fransgaard, T.; Thygesen, L. C.; Gögenur, I.
Abstract: Aim: The primary aim of the study was to determine whether preexisting diabetes is associated with increased 30‐day mortality after curative resection of colorectal cancer (CRC). The association between antidiabetic treatment and 30‐day mortality was also examined. Method: Patients diagnosed with CRC between 1 January 2003 and 31 December 2012 were identified through the Danish Colorectal Cancer Group National Clinical Database (DCCG). The Danish National Patient Register (NPR) collated all hospital contacts in Denmark and the diagnosis of diabetes was identified by combining NPR data with the use of antidiabetic drugs identified through the Danish National Prescription Registry and DCCG. The 30‐day mortality was examined by the Kaplan–Meier method with the log‐rank test and the Cox regression model used to test statistical significance. Results: The study included 29 353 patients, of whom 3250 had preexisting diabetes. The 30‐day mortality was significantly increased in patients with CRC and preexisting diabetes (adjusted hazard ratio 1.17, 95% CI 1.01–1.35, P = 0.03). The type of antidiabetic medication used was not associated with 30‐day mortality. Conclusion: Preexisting diabetes was associated with a higher short‐term mortality in patients with CRC. No association between the type of antidiabetic medication and short‐term mortality could be shown.